Study on the time of emergence of the first generation of raspberry cane midge (Resseliella theobaldi BARNES) - Sipos, K.; Pénzes, B. (International Journal of Horticultural Science, 2010)
The raspberry cane midge (Resseliella rheohaldi BARNES) is a major pest of raspberry in Europe. The accurate prediction of adult midge emergence is an important part of integrated raspberry protection. Calculation of the accumulated effective temperature may be used in prediction. The values of the critical accumulated effective temperature needed for the first flight of the midge differ in the European regions. In our experiments we investigated the first generation of the midge in Hungary. Our results show that the critical accumulated effective temperature for the first flight was the lowest compared with results received in other European countries. The emergence of males of the first generation was found at 145-194 day °C, and females started laying eggs a few days later.